Auto-Phase-Locked Time-Resolved Luminescence Detection: Principles, Applications, and Prospects - Deng, Qisheng; Zhu, Zece; Shu, Xuewen (Frontiers in Chemistry, 2020)
Time-resolved luminescence measurement is a useful technique which can eliminate the background signals from scattering and short-lived autofluorescence. However, the relative instruments always require pulsed excitation sources and high-speed detectors. Moreover, the excitation and detecting shutter should be precisely synchronized by electronic phase matching circuitry, leading to expensiveness and high-complexity. To make time-resolved luminescence instruments simple and cheap, the automatic synchronization method was developed by using a mechanical chopper acted as both of the pulse generator and detection shutter. Therefore, the excitation and detection can be synchronized and locked automatically as the optical paths fixed. In this paper, we first introduced the time-resolved luminescence measurements and review the progress and current state of this field. Then, we discussed low-cost time-resolved techniques, especially chopper-based time-resolved luminescence detections. After that, we focused on auto-phase-locked method and some of its meaningful applications, such as time-gated luminescence imaging, spectrometer, and luminescence lifetime detection. Finally, we concluded with a brief outlook for auto-phase-locked time-resolved luminescence detection systems.